Silence in philosophy, literature, and art - Bindeman, Steven L. (Value Inquiry Book Series, 2017)
Silence exists at the edge of the world, where words break off and meaning fades into ambiguity. The numerous treatments of silence in Steven L. Bindeman's Silence in Philosophy, Literature, and Art question the misleading clarity of certainty, which persists in the unreflective discourse of common experience. Significant philosophical problems, such as the limits of language, the perception of sound and the construction of meaning, the dynamics of the social realm, and the nature of the human self, all appear differently as a consequence of this questioning. Silence is shown to have two modes, disruptive and healing, which work together as complementary stages within a creative process. The interaction between these two modes of silence serves as the dynamic behind the entire work.